2021
DOI: 10.1111/ahe.12734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Lingual Papillae in the sugar glider (Petaurus breviceps) by scanning electron microscopy and light microscopy

Abstract: A morphological description of the sugar glider's (Petaurus breviceps) tongue was obtained from five individual sugar gliders and analysed under a scanning electron microscope and a light microscope using four methods of staining. The tongue has a noticeably elongated structure with three regions: apex, corpus and radix. Transition to the corpus is indicated by the sulcus medianus linguae and the frenulum on its ventral surface. The dorsal tongue displayed a raised mucous membrane manifesting as a type of papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…whether they are carnivores, omnivores or herbivores) as well as their environments and habitats, which may play a partial role in the evolution of the tongue's structure (Iwasaki et al, 2019). Such an adaptation based on diet, environment or habitat has been described in various studies, especially on mammals, such as goats (Mahdy et al, 2020), lemurs (Pastor et al, 2011), pumas (Erdoğan et al, 2017), sugar gliders (Damia et al, 2021) and several other carnivores, including polar bears, marsupials and bats (Emura et al, 2017;Goździewska-Harłajczuk et al, 2020;Gunawan et al, 2019;Saragih et al, 2020). Tongue morphology revealed a relationship between changes in habitat and changes in the appearance of the tongue; the transition from a freshwater (moist or wet) environment to a terrestrial (dry) environment resulted in the keratinization of the lingual epithelium (Iwasaki, 2002).…”
mentioning
confidence: 99%
“…whether they are carnivores, omnivores or herbivores) as well as their environments and habitats, which may play a partial role in the evolution of the tongue's structure (Iwasaki et al, 2019). Such an adaptation based on diet, environment or habitat has been described in various studies, especially on mammals, such as goats (Mahdy et al, 2020), lemurs (Pastor et al, 2011), pumas (Erdoğan et al, 2017), sugar gliders (Damia et al, 2021) and several other carnivores, including polar bears, marsupials and bats (Emura et al, 2017;Goździewska-Harłajczuk et al, 2020;Gunawan et al, 2019;Saragih et al, 2020). Tongue morphology revealed a relationship between changes in habitat and changes in the appearance of the tongue; the transition from a freshwater (moist or wet) environment to a terrestrial (dry) environment resulted in the keratinization of the lingual epithelium (Iwasaki, 2002).…”
mentioning
confidence: 99%
“…The tongue morphology, in its macroscopic structure (tongue papillae types, shape, function, and distribution) in vertebrates, varies to fit their diets (i.e., whether they are carnivores, omnivores, or herbivores) as well as their environments and habitats, which may have played a partial role in the evolution of the tongue's structure (Iwasaki et al 2019). Such an adaptation based on the diet, environment, or habitat has been described in various studies, especially in mammals, such as goats (Mahdy et al 2021), pumas (Erdogan et al 2018), sugar gliders (Damia et al 2021), and several other carnivores, including polar bears, marsupials, and bats (Emura et al 2017;Gozdziewska-Harlajczuk et al 2020;Gunawan et al 2020). In a study, the tongue morphology revealed a relationship between changes in the habitat and changes in the appearance of the tongue; the transition from a freshwater (moist or wet) environment to a terrestrial (dry) environment resulted in the keratinisation of the lingual epithelium (Iwasaki 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the environment and or habitats also take part in the tongue morphology evolution (Iwasaki et al 2019;Williams 2019). Furthermore, morphology, distribution, amount and the type of vertebrate lingual papillae are mainly influenced by diet (Pastor et al 2011;Iwasaki 2019;Damia et al 2021).…”
Section: Introductionmentioning
confidence: 99%